2010
DOI: 10.1542/peds.2009-3027
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of 13-Valent Pneumococcal Conjugate Vaccine in Infants and Toddlers

Abstract: PCV13 will be as effective as PCV7 in the prevention of pneumococcal disease caused by the 7 common serotypes and could provide expanded protection against the 6 additional serotypes. The PCV13 safety profile was comparable to that of PCV7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(127 citation statements)
references
References 28 publications
8
112
2
5
Order By: Relevance
“…In the PCV7 group, a correlation between the IgG and OPA levels was observed for the PCV7 serotypes and cross-reacting serotype 6A but not for 19A or the other PCV13 additional serotypes (with the exception of serotypes 3 and 7F after the toddler dose, but the immune responses for these serotypes were very low). The correlation between the OPA and ELISA results has also been demonstrated in other studies (4,5). The degree of OPA-to-IgG correlation can be affected by the OPA assay type used, e.g., killing OPA assay versus uptake assay.…”
Section: Discussionsupporting
confidence: 64%
“…In the PCV7 group, a correlation between the IgG and OPA levels was observed for the PCV7 serotypes and cross-reacting serotype 6A but not for 19A or the other PCV13 additional serotypes (with the exception of serotypes 3 and 7F after the toddler dose, but the immune responses for these serotypes were very low). The correlation between the OPA and ELISA results has also been demonstrated in other studies (4,5). The degree of OPA-to-IgG correlation can be affected by the OPA assay type used, e.g., killing OPA assay versus uptake assay.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, despite an effectiveness of 26% (95% CI, Ϫ45% to 62%) as estimated by U.S. Centers for Disease Control and Prevention (41), the vaccine was not able to prevent the increase in 19A IPD (16,21,24). Previous studies by Pfizer, Inc. showed that over 80% of subjects vaccinated with three doses of 7vCRM had antibody concentrations against serotype 19A that reached the antibody threshold, whereas only approximately 17% of the subjects had functional antibodies when measured using the OPA assay (4,17,47). These and our results support the conclusion that a large fraction of the crossreactive antibodies induced by 7vCRM against serotype 19A are nonfunctional.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, recent epidemiological data suggested that the administration of PCV7 has led to increases in the colonization of the nasopharynx by S. aureus and nonvaccine strains of S. pneumoniae, which may contribute to vaccine-resistant OM and other infections (20,149). In spite of this, a PCV13 vaccine, containing additional antigens for six other common pneumococcal strains, has recently been cleared for use in the United States and several other countries (223). Initial studies have shown similar safety and efficacy in priming antibody responses to the same degree as the PCV7 vaccine; follow-up studies will further clarify the success of this current vaccine design in reducing overall invasive pneumococcal morbidity (157).…”
Section: Considerations For Design and Use Of Polymicrobial Vaccinesmentioning
confidence: 99%